Analysis of landscape microclimate and green space transformation strategy for old residential areas——case: Luoliu community - Li Yihan; Wang Jingjing; Gou Aiping; Wang Jiangbo (E3S Web of Conferences)
As an old community, Luoliu community is representative in Shanghai. Traditional infrastructure is not combined with public space and green space layout, which makes the climate resilience of the old residential area urgently need to be improved. Through questionnaire survey, field measurement, combined with Envi-met to simulate microclimate changes and formulated green space resilience transformation strategies. Microclimate factors such as temperature, humidity, wind speed and wind direction change with the spatial distribution and vegetation structure. First, the walls of buildings are most vulnerable to the shadow of buildings. The microclimate of the building enclosed green space is stable, but its toughness is poor. Parallel green space can restrain the temperature rise to a certain extent, it has strong space toughness. Green enclosure space is also closed, usually covered with green plants. Although it can reduce the impact of solar radiation, overgrown and untrimmed trees will become an obstacle to air ducts. Ventilation should be the priority. Second, the canopy and vertical structure of green plants should be reasonable. Third, the combination layout of the dominant wind direction and the residential complex shall be considered comprehensively to plan the public facilities and sidewalks.